Microsoft Windows 3.1 programmer's reference (Microsoft Press, 1992)
An alphabetical reference to the entire Windows 3.1 API especially for C and C++ programmers containing the entire set of calls for creating the framework of an application: generating windows, manipulating graphics, controlling basic system services, and applications in memory.